468 UTEROPLACENTAL INSUFFICIENCY AFFECTS THE CEREBRAL GLUCOCORTICOID RECEPTOR TRANSCRIPTION INITIATION SITE. (10th December 2015) - Ke, X.; McKnight, R. A.; Nelson, L.; Yu, X.; Wang, L.; Lane, R. H.
Abstract : Background: IUGR increases the risk for neurodevelopmental delay and causes neuroendocrine reprogramming. We have previously demonstrated that the hippocampus is vulnerable to IUGR induced insult. The hippocampus contains high levels of glucocorticoid receptor (GR) and is an important regulator of glucocorticoid homeostasis. Expression of GR is complex, involving regulation at both translational and transcriptional levels. Control of transcription of the rat GR transcript relies in part upon the regulation of multiple alternative initiation sites that are tissue specific. Each site generates a unique exon 1, with exon 1.10 being the predominant species. Objective: We therefore hypothesized that IUGR induced stress causes an increase in GR levels within the IUGR rat brain, and this increase would be associated with a change in the GR initiation start site. Methods: Bilateral uterine artery ligation was performed on d19 pregnant Spague-Dawley rats to induce IUGR through uteroplacental insufficiency (n=6 litters). Pups were delivered by cesarean at term. Brains were harvested and snap frozen. Total GR protein was quantified by Western blot. GR expression in the brain was localized by immunohistochemistry (IHC). Cerebral GR and GR exon 1 splice variant mRNA levels were quantified using real-time RT-PCR. Results: IUGR increased total GR protein levels to 142 ± 9.2% of control values (p≤0.01). IHC showed that the expression of GR was higher in hippocampus of IUGR rat brains as compared to controls. IUGR increased total cerebral GR, GR exon 1.5 and exon 1.6 mRNA levels to 186 ± 29%*, 181± 12%** and 128±7%* of control values respectively (*p≤0.05; **p≤ 0.01). IUGR did not alter the GR exon 1.10 and exon 1.11 mRNA levels. Conclusion: Uteroplacental insufficiency causes an increase in GR expression within the hippocampus of the rat brain. The increase in GR mRNA levels is due in part to an increase in GR transcription initiation at the alternative transcription start sites 1.5 and 1.6. We speculate that determination of the pathways which switch the GR cerebral initiation sites will play a role in the neuroendocrine reprogramming known to occur in the IUGR newborn.